Knowledge, Attitudes, and Prevalence of Menopausal Symptoms among Perimenopausal and Postmenopausal Women – A Mixed Method Study from Tamil Nadu - Giddaluru Bhavya Muralikrishna; Karthiga Prabhu; Shanmugapriya; Gowthaman Sankar (Journal of Mid-Life Health, 2025)
Background: The age at which menopause occurs varies widely among different populations around the world, and the severity of menopausal symptoms often increases with age. Although menopause is not classified as an illness, it is associated with higher rates of mortality and morbidity among women. Many women go through menopause without adequate knowledge of its health implications. It is essential for women to be informed about the symptoms and complications of menopause so they can manage it effectively and seek appropriate treatment. Without this knowledge and with negative attitudes towards menopause, women may face difficulties during the postmenopausal period. Objectives: This study aims to assess the prevalence of menopausal symptoms and to evaluate the knowledge and attitudes of peri- and postmenopausal women toward menopause. Materials and Methods: This mixed-method study was conducted at a single center in a major tertiary care hospital located in Chengalpattu, Kanchipuram, Tamil Nadu, from February 2023 to October 2024. A total of 300 women experiencing perimenopausal and menopausal symptoms were included through convenience sampling. Ethical guidelines established by the institutional ethics committee were followed throughout the study. We utilized the Menopause Rating Scale (MRS), a self-reported and validated tool, to assess the severity of menopausal symptoms reported by the participants. Results: The most common symptoms reported by perimenopausal women included sleep problems (53.4%), hot flashes (50%), anxiety (67.8%), irritability (65.6%), bladder issues (46.7%), and sexual discomfort (44.4%). In postmenopausal women, frequently reported symptoms were joint pain (56.2%), depressive mood (70%), physical and mental exhaustion (63.4%), vaginal dryness (64.8%), and sexual problems (58.1%). Overall, severe menopausal symptoms were more prevalent among postmenopausal women compared to those in the perimenopausal stage, with a statistically significant difference (P < 0.05). Binomial logistic regression analysis showed that age (adjusted odds ratio [AOR] – 1.78), parity (AOR – 2.49), and poor knowledge about menopause (AOR – 2.78) were significant risk factors associated with the severity of menopausal symptoms. Conclusion: This mixed-method study found significant differences in menopausal symptoms, knowledge, and attitudes between peri- and postmenopausal women. In postmenopausal women, higher mean total MRS scores indicated severe somatic, psychological, and urogenital symptoms. We found that menopausal women need tailored education and culturally sensitive support to close knowledge gaps, promote positive attitudes, and meet complex needs.